دور دار الوثائق القومیة فى التسویق للتراث الوطنى الوثائقى فى مصر : دراسة تحلیلیة - د. مریم صالح منصور (المجلة الدولية لعلوم المكتبات والمعلومات)
National archives play a pivotal role in documenting the historical memoryof human beings and have the capacity to change the social, economic andpolitical development of the people. So it is critical that they are visible,accessible and used. Her ability to make available the documentary heritage inher custody is the only basis to justify her presence and importance in society.Reaching and availability are the function of Dar Alwthayq Alqwmy of the mostimportant and the most difficult at the same time. Therefore, this study sought toknow the extent to which the National Archives has made its documentaryheritage available and usable by all members of the community, and to monitorthe challenges it faces in order to achieve this with the conception of a successfulmarketing plan that achieves various goals. The study revealed the absence ofthe term (public archival programming) from the Arab arena, and the study foundthat marketing activities are influenced by legislation, policies and personnel skillsand study the needs of users and cooperation and technology. The studyrevealed the absence of a special department for marketing and awareness ofthe national heritage in the Dar Alwthayq Alqwmy and the lack of budgetallocated for marketing and the lack of a website for Dar Alwthayq Alqwmyweakened its mission in promoting the national heritage documentary. The studyrecommended the need to develop policies and modernize legislation on freedomof access to the national documentary heritage and to put into practice theprinciples set by the International Council of Archives (ICA) for free access todocumentary heritage.